O consequencialismo e não consequencialismo em ética animal - Lima, Arthur Falco de (2017)
Peter Singer and Gary L. Francione, contemporary philosophers, espouse the term speciesism by referring to ethical theories that somehow deprive the interests of other species, depriving them of the scope of morality, and provide solid arguments, each one in your own way, in favor of an extension of our moral community to beings of another species. Singer defends a consequentialist approach, more specifically, preference utilitarianism. Francione, in turn, adopts a deontological perspective, based on rights approach. There is, in general, a natural tension between these two normative theories due to the fact that one is based on the defense that the foundation of our moral obligations and the correctness of action are inevitably connected with the resulting consequences for the interests of all affected, while the other, on the other hand, thinks that we must protect interests, regardless of the consequences of our actions, namely, even when acting in a certain way can bring benefits to other people. In this work we show that although their difference is essential to understand the debate between them, it does not antagonistically separate them from in two opposite sides. On the contrary, we conclude that the two authors defend a shared claim that we should abolish the institutionalized exploitation of non-human animals by, for example, adopting a vegan diet and boycotting the other customary practices we make.